ANALISIS DAN PERBAIKAN KERUSAKAN SLOTTING ATTACHMENT MESIN FRAIS MENGGUNAKAN PENDEKATAN CORRECTIVE MAINTENANCE DAN TAHAPAN DMAIC-SIX SIGMA - Muhammad Faris Agustiansyah Faris; Jeni Amriansyah; Indra Feriadi; Muhammad Rivai (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Repeated failure one of the Slotting Attachment units hampered student practice and production activities at the Polmanbabel machining laboratory. This study aims to determine the cause of the damage Slotting Attachment and fix it to normal condition. The research method using corrective maintenance approach with customized DMAIC-Six Sigma stages to identify and repair the cause of the damage. Analysis of the failure causes using the 5 why analysis method. The results of the analysis found that the cause of the damage started from the broken component of the wedges and then spread to the damage/wear of the shaft connector, bush, and bush pivot components. Repair of components is carried out by replacing the wedges with stronger materials, making new shaft connectors, smoothing the damage to the bush surface and metalizing the bush pivot surface. The function test shows that the component assembly and Slotting unit can function properly, however the temperature test indicate that the unit's performance still needs further improvement. The corrective maintenance approach with the DMAIC-Six Sigma stages can be used to identify and repair machine damage.